Klasifikasi Inceptisol Pada Ketinggian Tempat yang Berbeda di Kecamatan Lintong Nihuta Kabupaten Hasundutan - Samuel Evans Ketaren; Posma Marbun; Purba Marpaung (Universitas Sumatera Utara, 2014)
This research aims to classify inceptisol soil at sub-district of Lintong Ni Huta, Regency ofHumbang Hasudutan on the various elevation. On the elevation of 1200-1300, 1300-1400, 1400-1500, and >1500m on above sea level. The sampling of soil was took at 3 soil profile holes on FieldMap unit and Key to Soil Taxonomy 2010 . Of the result of this research, it obtain the classification ofprofile 1, 2, and 3 with Ordo, Sub Ordo, and Great Groupin the same is Inceptisol, Udept,and Dystrudept. OnSub Group category the classification of profile 1 is Psammentic Dystrudept. On Sub Group category theclassification of profile 2 is Pachic Dystrudept. On Sub Group category the classification of profile 3 isFluventic Dystrudept.Key words : Various elevation, Inceptisol